Learning to Move an Object by the Humanoid Robots by Using Deep Reinforcement Learning - Aslan, Simge Nur; Tasci, Burak; Ucar, Aysegul; Guzelis, Cuneyt (Ios Press, 2021)
This paper proposes an algorithm for learning to move the desired object by humanoid robots. In this algorithm, the semantic segmentation algorithm and Deep Reinforcement Learning (DRL) algorithms are combined. The semantic segmentation algorithm is used to detect and recognize the object be moved. DRL algorithms are used at the walking and grasping steps. Deep Q Network (DQN) is used to walk towards the target object by means of the previously defined actions at the gate manager and the different head positions of the robot. Deep Deterministic Policy Gradient (DDPG) network is used for grasping by means of the continuous actions. The previously defined commands are finally assigned for the robot to stand up, turn left side and move forward together with the object. In the experimental setup, the Robotis-Op3 humanoid robot is used. The obtained results show that the proposed algorithm has successfully worked.
17th International Conference on Intelligent Environments (IE) -- JUN 21-24, 2021 -- Middlesex Univ Dubai, ELECTR NETWORK
Keywords: Humanoid robots; DQN; DDPG; deep semantic segmentation; object manipulation; locomotion